Genetic and morphological variants of Acidovorax avenae subsp. avenae cause red stripe of sugarcane in China - Zhao, Jian-Ying; Chen, Juan; Hu, Zhong-Ting; Li, Juan; Fu, Hua-Ying; Rott, Philippe C.; Gao, San-Ji (Frontiers in Plant Science, 2023)
Sugarcane (Saccharum spp.) is an important cash crop for production of sugar and bioethanol. Red stripe caused by Acidovorax avenae subsp. avenae (Aaa) is a disease that occurs in numerous sugarcane-growing regions worldwide. In this study, 17 strains of Aaa were isolated from 13 symptomatic leaf samples in China. Nine of these strains produced white-cream colonies on nutrient agar medium while the other eight produced yellow colonies. In pairwise sequence comparisons of the 16S-23S rRNA internally transcribed spacer (ITS), the 17 strains had 98.4-100% nucleotide identity among each other and 98.2-99.5% identity with the reference strain of Aaa (ATCC19860). Three RFLP patterns based on this ITS sequence were also found among the strains of Aaa obtained in this study. Multilocus sequence typing (MLST) based on five housekeeping genes (ugpB, pilT, lepA, trpB, and gltA) revealed that the strains of Aaa from sugarcane in China and a strain of Aaa (Aaa30179) isolated from sorghum in Brazil formed a unique evolutionary subclade. Twenty-four additional strains of Aaa from sugarcane in Argentina and from other crops worldwide were distributed in two other and separate subclades, suggesting that strains of A. avenae from sugarcane are clonal populations with local specificities. Two strains of Aaa from China (CNGX08 forming white-cream colored colonies and CNGD05 forming yellow colonies) induced severe symptoms of red stripe in sugarcane varieties LC07-150 and ZZ8 but differed based on disease incidence in two separate inoculation experiments. Infected plants also exhibited increased salicylic acid (SA) content and transcript expression of gene PR-1, indicating that the SA-mediated signal pathway is involved in the response to infection by Aaa. Consequently, red stripe of sugarcane in China is caused by genetically different strains of Aaa and at least two morphological variants. The impact of these independent variations on epidemics of red stripe remains to be investigated.